2017
DOI: 10.1016/j.ceb.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet growth: regulation of a dynamic organelle

Abstract: Intracellular lipid droplets (LDs) are remarkably dynamic and complex organelles that enact regulated storage and release of lipids to fulfil their fundamental roles in energy metabolism, membrane synthesis and provision of lipid-derived signaling molecules.Although small LDs are observed in all types of eukaryotic cells, it is adipocytes that present the widest range of sizes up to the massive unilocular droplet of a white adipocyte. Our knowledge of the proteins and associated processes that control LD dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
1
39
0
2
Order By: Relevance
“…Because T N and T CM , but not T EM , cells could compensate for low glucose by augmenting oxidative phosphorylation in a fatty-acid-dependent manner, we wanted to examine the supply of lipids stored within the cell. Lipid droplets are dynamic organelles that play a key role in the regulation of lipid metabolism and serve as a ready to use source of lipids ( Barneda and Christian, 2017 ). We first isolated total CD4 T cells and examined the number of lipid droplets in resting and activated cells in both optimal and low glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Because T N and T CM , but not T EM , cells could compensate for low glucose by augmenting oxidative phosphorylation in a fatty-acid-dependent manner, we wanted to examine the supply of lipids stored within the cell. Lipid droplets are dynamic organelles that play a key role in the regulation of lipid metabolism and serve as a ready to use source of lipids ( Barneda and Christian, 2017 ). We first isolated total CD4 T cells and examined the number of lipid droplets in resting and activated cells in both optimal and low glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Given that our datamining efforts identified TFAP2 family members as putative transcription factors regulating lipid droplet proteins and that TFAP2C was among the most upregulated transcription factors in response to Wnt3a ( Figure 2B ), we next investigated whether TFAP2 family members played a direct role in regulating lipid droplets. To this end, we tested the ability of TFAP2A to directly bind to the promoter region of known lipid droplet, and lipid metabolic genes containing a predicted TFAP2 consensus site by ChIP-PCR ( Figure 2C ), including the enzymes ACSL3, ACSL4, AGPAT2, AGPAT3, LPCAT2, and MGLL, and the lipid droplet resident proteins PLIN3, PLIN4, PNPLA2, and PNPLA3 ( Meyers et al, 2017 ; Barneda and Christian, 2017 ). Indeed, we found that the TFAP2A protein was able to bind the upstream promoter of all the genes we tested, supporting the notion that expression was controlled by TFAP2 family members.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, LDs consist of a neutral lipid core uniquely enclosed by a single phospholipid monolayer and coated with a diverse array of 'coat' proteins that either bind the LD surface directly or embed themselves into the monolayer (Murphy, 2012). The formation of LDs occurs de novo between the leaflets of the endoplasmic reticulum (ER) membrane in what is considered to be a complex, multistep process (Thiam and Forêt, 2016;Barneda and Christian, 2017;Chen and Goodman, 2017). Briefly, the synthesis and accumulation of TAG within the ER bilayer serves to initiate the core of a nascent LD, which is thought to occur at specialized sites (subdomains) of the ER.…”
Section: Introductionmentioning
confidence: 99%